CONTACT INTERACTION INVESTIGATION OF TARGET END FACE OF ULTRASONIC CONVERTER INSTALLED ON PENDULUM SUSPENSION WITH RIGID BASIS - M. G. Kiselev; A. V. Drozdov; А. A. Novikov; A. A. Neskina; A. A. Stolarov (Наука и техника)
An investigation pertaining to contact interaction process of a target end face of the ultrasonic converter installed on pendulum suspension with a rigid basis is presented in the paper. The paper shows that substitution of traditionally applied precision rolling guides by a pendulum suspension of the ultrasonic converter allows significantly to simplify a process equipment design. A calculative model for contact interaction of an end face of the ultrasonic converter installed on a pendulum suspension  with a rigid basis and scheme of a mathematical  pendulum  that  corresponds are proposed in the paper and they permit to investigate an influence of pendulum suspension parameters and its loading conditions on the operational mode of an acoustic oscillatory system. The paper contains analytical dependences that make it possible to calculate time and power parameters in contact interaction of a target end face of the ultrasonic converter installed on a pendulum suspension with a rigid basis. These dependences take into account an amplitude of ultrasonic oscillations, converter weight, pendulum length and an angle of its deviation. The paper reveals that the application of the pendulum suspension of the ultrasonic converter allows to ensure a vibrating impact (operational) mode of interaction of a converter target end face with a rigid basis surface. Design variants of the pendulum suspension of the ultrasonic converter while using various elastic elements are proposed and analyzed in the paper and with due account of concrete processing conditions these variants allow to provide the required value of own oscillation frequency of an acoustic system and also to create necessary value of a preliminary tightness in it.